Beyond nutritional: a case series of thalassemia trait - Tharakan, Alisha Rahel; Cherian, Carol Sara (International Journal of Contemporary Pediatrics, 2026)
Microcytic anemia in children is frequently attributed to iron deficiency, yet not all cases improve with adequate iron therapy. When anemia persists despite normal iron stores, other causes-particularly hemoglobinopathies-must be considered. This report describes three children who presented with ongoing microcytic hypochromic anemia that did not resolve with appropriate iron supplementation. All had documented treatment adherence and iron profiles within the expected range for sufficiency. Each child underwent a structured evaluation. Two were found to have elevated HbA2 levels on hemoglobin electrophoresis, establishing a diagnosis of beta-thalassemia trait. The third child had nondiagnostic electrophoresis findings but demonstrated heterozygous deletions in the HBA1 and HBA2 genes on molecular analysis, confirming alpha-thalassemia trait. None of the children exhibited organomegaly, significant clinical symptoms, or dysmorphic features, and their growth parameters were appropriate for age. The consistent finding across all cases was persistent microcytosis despite biochemical evidence of adequate iron. These cases emphasize the importance of considering thalassemia traits when confronted with pediatric anemia that does not respond as expected to iron therapy. Recognizing characteristic red-cell indices and pursuing targeted investigations can prevent repeated or unnecessary treatment and allow families to receive appropriate genetic counseling. Early and accurate identification of hemoglobinopathies contributes to better long-term management and ensures that healthcare resources are used appropriately.